Bernese Periacetabular Osteotomy in a Hip Extra-Articular Resection Followed by Reconstruction Using an Extracorporeal Irradiated Acetabulum Autograft with Megaprosthesis, for Proximal Femur Osteosarcoma in a Pediatric Patient - Barro, Victor (Case Rep Med, 2015)
Osteosarcoma is the most common primary malignant tumour of bone. The oncologic surgery of a proximal femur osteosarcoma affecting the hip joint can be very challenging. We present an 8-year-old boy with a 5-month history of right hip pain. Radiographs and magnetic resonance imaging (MRI) showed a lytic lesion of the proximal femur extending 13 cm to the diaphysis. Histological evaluation was consistent with high-grade osteoblastic osteosarcoma. After completing chemotherapy we performed an extra-articular resection of the hip. Reconstruction was accomplished by reimplanting the acetabulum after irradiation and modular proximal femur megaprosthesis. Endoprosthetic reconstruction following proximal femur resection is a good treatment alternative achieving good postoperative function. Extra-articular resection of the hip using a periacetabular osteotomy technique enabled us to achieve wide margins and leave an intact posterior column to optimize acetabular reconstruction stability. Extracorporeal irradiation and reimplantation is a valuable treatment option in a situation such as this where allograft geometric fit is a priority. We conclude that an extra-articular resection of the hip, followed by reconstruction with an extracorporeally irradiated acetabulum and a proximal femur modular megaprosthesis, is a useful combined treatment option for malignant lesions involving the hip joint, especially in paediatric patients.